La missione della Chiesa ortodossa nel mondo contemporaneo (Stato, Chiese e pluralismo confessionale, 2017)
Contributo sottoposto a valutazioneSOMMARIO:Â 1. Il tema. â 2. Il valore della persona umana. â 3. LibertÃ  e responsabilitÃ . â 4. Pace e giustizia. â 5. Pace e prevenzione della guerra, condanna delle discriminazioni. - 6. La missione della Chiesa ortodossa, testimonianza di amore nel servizio.The Mission of the Orthodox Church in todayâs WorldABSTRACT: This paper expresses the opinion of the Orthodox Churches which met in Crete on the occasion of the pan-Othodox Synod from June 18-26 2016.Â The topic of that meeting was the increasing pertinence, in todayâs contemporary world, of the human condition, justice, the use of natural resources and peace. Furthermore central was the issue of how to position the Orthodox Churches as custodians of traditional evangelical values and traditions.